2019
DOI: 10.1177/0022002719879217
|View full text |Cite
|
Sign up to set email alerts
|

Angry or Weary? How Violence Impacts Attitudes toward Peace among Darfurian Refugees

Abstract: Does exposure to violence motivate individuals to support further violence or to seek peace? Such questions are central to our understanding of how conflicts evolve, terminate, and recur. Yet, convincing empirical evidence as to which response dominates—even in a specific case—has been elusive, owing to the inability to rule out confounding biases. This article employs a natural experiment based on the indiscriminacy of violence within villages in Darfur to examine how refugees’ experiences of violence affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 52 publications
1
38
0
Order By: Relevance
“…In this section we briefly introduce the applied example that is used throughout the paper. (We describe only the most relevant details; further information is available in Hazlett (2019).) This serves as a background to illustrate how the tools that are developed here can be applied to address problems that commonly arise in observational research.…”
Section: Running Examplementioning
confidence: 99%
“…In this section we briefly introduce the applied example that is used throughout the paper. (We describe only the most relevant details; further information is available in Hazlett (2019).) This serves as a background to illustrate how the tools that are developed here can be applied to address problems that commonly arise in observational research.…”
Section: Running Examplementioning
confidence: 99%
“…In stark contrast, other studies have found that violence exposure can spur pro-peace attitudes. For example, Hazlett (2020) found that refugees from Darfur who were directly affected by the wave of violence in the early 2000s were less supportive of harsher punishment and more likely to believe that peace was possible. Still other studies have yielded mixed results.…”
Section: Exposure To Violence and Attitudes Toward Peacementioning
confidence: 99%
“… 12 In a related finding, Hazlett (2015) finds that South Sudanese refugees who had been victimized by violence are more optimistic about the prospect of making peace with their enemies and less likely to believe they should be executed.…”
mentioning
confidence: 99%